Deviant workplace behavior among law enforcement officers in the Royal Malaysian Police - Sathappan, Malini (2017)
Deviant workplace behavior (DWB) exists in every occupation including law enforcement agency. By discovering DWB it may promote ethical awareness among employees and it will promote positive behavior which can enhance the image and reputation of Royal Malaysian Police (PDRM) in public. Despite many studies that have been conducted on DWB very little studies have been done on DWB in the law enforcement agency in Malaysia. This has resulted in critical gaps to understand how DWB is experienced by law enforcement officers in Malaysia. The main purpose of this study is to understand the experiences of deviant workplace behavior among law enforcement officers and to identify the concept, types and causes of DWB. This study was carried out through an in-depth exploration of three research questions. The questions are: (1) What is the meaning of deviant workplace behavior among law enforcement officers? (2) What are the conditions contributing to workplace deviant behavior among law enforcement officers? (3) Why law enforcement officers engage in deviant workplace behavior? A qualitative research methodology using phenomenological case study approach was selected as this approach has proved to be suitable for the study of a phenomenon of this nature. Data was generated from fourteen respondents who are law enforcement officers at PDRM. The primary data collection method employed to attain the purpose of the study was in-depth interviews with the participants. The findings generated three concepts of deviant workplace behavior, namely 1) violation of norms, 2) violation of rules and 3) abuse of power. The findings also revealed two themes for identifying types of deviant behavior which consists of 1) organizational deviance and 2) interpersonal deviance. This is followed by two themes which were developed to explain the causes of deviant workplace behaviour that is 1) individual / internal factors and 2) external factors. The study concluded that DWB was understood as disobeying “Perintah Tetap Ketua Polis Negara” rules. There were two types of DWB firstly harming the image of the organization secondly harming co-workers that occur among law enforcement officers in PDRM. Finally most of the informants revealed individual cause is a major cause of DWB such as lack of up bringing and teaching, financial issues, stress and lack of self integrity compared with external cause such as environment, cost of living, family and public. This study has provided valuable information which will be beneficial to law enforcement stakeholders and the study has also contributed to the understanding real life experiences of officers who have reported DWB cases.